Lobbying and democracy in Germany - Zumpfort, Wolf-Dieter (2020)
Interest representation is a constitutive element of German democracy and as such a key part of the political decision making process. But the public opinion on lobbying is marked by precudices and accusations in particular of intransparency, patronage and corruption. Consequently repeated calls for rules and laws for more transparency and control are to be heard from different sides. It is obvious that key conditions for lobbying, which is acceptable in a democracy, must be transparency and comprehensibility for the public. Yet, some approaches of self-regulation and legal framework exist or respectively are in progress.